THE REGIONAL REPRESENTATIVE COUNCIL IN INDONESIA: A VIEW OF UNRESOLVED PROBLEMS - Diya Ul Akmal (Res Justitia : Jurnal Ilmu Hukum, 2022)
The Regional Representative Council in Indonesia was established as part of constitutional reform, and it is expected to be able to address current issues with regional aspirations absorption. The Regional Representative Council is still lacking in its presence as a State Institution after nearly 18 years of existence. This is due to the fact that Indonesia uses a Soft Bicameral System in the Legislative Chamber. The People's Representative Council wields more power in the Legislative process than the Regional Representative Council. This is evident from the Constitution's and other regulations' limited authority. It is critical to strengthen the Regional Representative Council's authority as a State Institution with equal standing to the People's Representative Council. Indeed, there is a double check on the draft law between the two Legislative Chambers under the Bicameral Concept. The goal is to achieve good legal formation. Furthermore, given the community's current social situation, it is necessary to monitor indigenous peoples' protection. The Regional Representative Council must be the first line of defense in the region, overseeing all aspects of life, including indigenous peoples